Engineered E. coli OMVs Carrying the Membrane-Binding hGC33 Fragment Precisely Target Liver Cancer and Effectively Treat Tumor - Deng Y; Yang B; Yang Z; Xiao H; Zou Y; Zou C; Yang S; Sun X; Wang Y; Bai J; Fang L; Wang Z (International Journal of Nanomedicine)
Yufei Deng,1 Bangya Yang,1 Zelan Yang,1 Hanyu Xiao,1 Yan Zou,1 Cheng Zou,1 Song Yang,1 Xi Sun,1 Yiting Wang,1 Jin Bai,1 Liaoqiong Fang,1,2 Zhibiao Wang1,2 1State Key Laboratory of Ultrasound in Medicine and Engineering, College of Biomedical Engineering, Chongqing Medical University, Chongqing, 400016, People’s Republic of China; 2National Engineering Research Center of Ultrasound Medicine, Chongqing, 401121, People’s Republic of ChinaCorrespondence: Zhibiao Wang, Email wangzb@cqmu.edu.cn Liaoqiong Fang, Email lqfang06@163.comBackground: Glypican-3 (GPC3), which is a membrane-associated antigen that is overexpressed in hepatocellular carcinoma (HCC). hGC33, a humanized anti-GPC3 antibody, has been validated as a potential antibody drug with good antitumor activity by preclinical studies and the Phase II clinical trial. However, free drug usually lack good tumor penetration. Outer membrane vesicles (OMVs) that are secreted by Escherichia coli function as natural vectors for molecule delivery and mediators of biological signals across tissues. Our study aimed to engineer E. coli for use as a platform to precisely deliver the hGC33 single-chain variable fragment (hGC33-scFv) for the targeted treatment of HCC.Methods: In this study, we utilized E. coli BL21(DE3) to express Hbp-hGC33-scFv fusion protein and generated E. coli hGC33-OMVs. After isolation and characterization, we assessed their chemotaxis toward HepG2  cells by Transwell, coimmunoprecipitation (co-IP) to confirm hGC33-GPC3 binding, and immunofluorescence (IF) to evaluate the localization of hGC33 on OMV membranes. The in vivo efficacy was assessed in BALB/c nude mice harboring HepG2  cell-derived xenografts, and tumor targeting was analyzed with Cy7-labeled OMVs and live imaging. Proliferation assays, cell cycle analysis, and Wnt pathway expression analysis were performed to elucidate the underlying mechanisms.Results: hGC33-OMVs exhibited spherical bilayered nanostructures and displayed hGC33-scFv on their surface. hGC33-OMVs preferentially accumulated in tumors, significantly reducing tumor volume compared with controls and downregulating the proliferation markers Ki67 and PCNA. Transwell assays revealed increased tropism of hGC33-OMVs toward HepG2 cells, while Co-IP confirmed the direct interaction between hGC33 and GPC3. Meanwhile, hGC33-OMVs suppressed HepG2 cell proliferation, induced G1-phase arrest, and reduced Wnt3a, β-catenin, Cyclin D1, and C-myc expression.Conclusion: Engineered E. coli hGC33-OMVs effectively target HCC via the hGC33-GPC3 interaction, inhibit tumor growth by suppressing Wnt signaling, and demonstrate potential for use as a versatile platform for antibody delivery. Keywords: hepatocellular carcinoma, glypican-3, outer membrane vesicles, targeted therapy, Wnt signaling pathway